Global Trends in Employee Wellbeing Research: A Bibliometric Study - Loso Judijanto (Westscience Press, 2024)
This bibliometric study examines global trends in employee wellbeing research from 1990 to 2024, focusing on key themes such as burnout, work engagement, job satisfaction, leadership, and workplace environment. Using co-authorship networks, keyword co-occurrence analysis, and citation metrics, the study identifies influential authors, emerging trends, and underexplored areas in the field. Results show a significant increase in publications since 2017, with a growing focus on the psychological and emotional dimensions of wellbeing. Key findings highlight the positive impact of transformational leadership and supportive work environments, as well as the detrimental effects of toxic behaviors like abusive supervision and workplace bullying. The study also identifies gaps in the literature, particularly regarding the intersection of employee wellbeing and diversity, equity, and inclusion (DEI). This analysis provides a foundation for future research and emphasizes the critical role of employee wellbeing in fostering organizational success and sustainability.